Atypical Presentation of Kawasaki Disease With Coronary Artery Aneurysms in a 2.5-Month-Old Infant: A Case Report From Syria - Suzan Mahfoud; Aous Arous; Danial Antonios; Hussein Jasser; Abdulrahman Shbani (Clinical Medicine Insights: Case Reports)
Kawasaki disease (KD), a febrile vasculitis primarily affecting young children under 5, is commonly associated with coronary artery complications. This report describes the case of a 2.5-month-old infant presenting with a persistent 15-day fever, initially misidentified as pharyngitis and otitis media. Laboratory tests indicated significant leukocytosis, thrombocytosis, and increased C-reactive protein (CRP) levels. Echocardiography revealed coronary artery dilation and pericardial effusion, confirming a KD diagnosis. The infant received intravenous immunoglobulin (IVIG) and high-dose aspirin, which resolved the fever. Symptom recurrence necessitated additional IVIG and corticosteroid treatment. Subsequent imaging showed ongoing coronary dilation, emphasizing the risk of lasting vascular complications. This case underscores the diagnostic challenges of KD in infants, especially those with atypical presentations. Prompt diagnosis and treatment are critical to prevent serious complications such as coronary aneurysms. Healthcare providers should consider KD in infants with prolonged unexplained fevers to improve prognosis and minimize heart-related risks.